Lactobacillus species increase the survival of Galleria mellonella infected with Candida albicans and non-albicans Candida clinical isolates - Santos, Rafaella Braga [UNESP]; Scorzoni, Liliana [UNESP]; Namba, Andressa Mayumi [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Oxford University Press (OUP), 2019)
Investigation into new therapeutic strategies, such as the use of bacterial isolates with probiotic characteristics, has increased in importance due to the high incidence of Candida albicans and non-albicans Candida infections. This study evaluates Lactobacillus paracasei, Lactobacillus fermentum and Lactobacillus rhamnosus strains as prophylactic and therapeutic agents against infection caused by Candida albicans, Candida glabrata, Candida krusei, and Candida tropicalis in a Galleria mellonella model. Prophylactic treatment provided greater benefits during Candida spp. infection, increasing G. mellonella survival, compared to therapeutic treatment. This study demonstrated that the different Lactobacillus species are potent prophylactic agents of Candida species infection.
Keywords: Candida spp. probiotic; Galleria mellonella; Lactobacillus spp; Prophylactic treatment